The Practice of social research - Babbie, Earl R. (Wadsworth Cengage Learning, 2013)
Babbie emphasizes the process by showing you how to design and construct projects, introducing the various observation modes in use today, and answering critical questions about research methods--such as how to conduct online surveys and analyze both qualitative and quantitative data.